Government chancery contacts 1988 - Petersson, Olof (Uppsala University, 1991)
This survey forms part of the report on power 'Maktutredningen', and deals with Government Chancery contacts. The survey concerns office contacts such as telephone calls, meetings, letters etc., and they are divided into ten sections: contacts with cabinet ministers; under-secretaries of state; civil servants of the departments; committees, working parties and delegations; central government agencies and other public bodies; the parliament; political parties, organizations and associations; companies; mass media; and international contacts. The frequencies of contacts are measured by a summarized opinion on how often contacts were taken the last year: every day, every week, every month, a couple of times annually, seldom/never. Furthermore the respondent were asked about rank, departmental affiliation and unit.

Denna undersökning ingår som en delundersökning i Maktutredningen och handlar om regeringskansliets kontakter. Med kontakt avses personlig kontakt med företrädare för till exempel departement, myndighet, organisation, etc. Det kan röra sig om telefonsamtal, sammanträde, brev eller annat slag av kontakt. Undersökningen gäller kontakter i tjänsten och är uppdelad i tio avdelningar: kontakter med statsråd; statssekreterare; departementens tjänstemän; kommittéer, arbetsgrupper, delegationer etc.; myndigheter och andra offentliga organ; riksdagen; partier, organisationer och föreningar; företag; massmedia; och internationella kontakter. Kontakternas frekvens mäts med ett sammanfattande omdöme: hur ofta man under året haft respektive kontakt - i stort sett varje dag, i stort sett varje vecka, i stort sett varje månad, i stort sett en/ett par gånger per år, sällan/aldrig. Dessutom ställdes inledande frågor om den intervjuades tjänsteställning, departementstillhörighet och enhet.
Regeringskansliets kontakter 1988
Keywords: Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Public Administration Studies; Studier av offentlig förvaltning